Prevalence of tinea capitis and asymptomatic carriage amongst school going children - Ahmed, Ijaz; Ahmed, Zaffar; Nasreen, Sarwat (Journal of Pakistan Association of Dermatologists, 2017)
Background Tinea capitis is one of the most common dermatophytosis seen in school going children, with diverse clinical presentations and a worldwide prevalence. Causative fungi belong to Trichophyton and Microsporum species, but vary with geography and time. Clinically it is characterized by erythema, scaling, pruritus and alopecia. Moreover, the infection can exist as an asymptomatic carriage in children, which in turn may be a source for anthroponotic transmission of tinea capitis. Â Objective To see the frequency of tinea capitis and its asymptomatic carriage in school going children, thus correlating the frequency of disease and carriage rates. Â Patients and methods The current study was centered at Ali Bhai, Karachi Municipal Corporation School and students of the nearby schools in the residential area were sampled during the months of April and May 2004. Students with the consent of their parents were enrolled randomly. Both normal boys and girls and students suspected to be suffering from tinea capitis were included. Hair samples obtained from normal as well as diseased subjects by sterile hairbrush technique were subjected to light microscopy after treating with 25% potassium hydroxide and inoculated onto Sabouraudâ€™s medium for culture. Colonial morphology and microscopy specified the causative organisms in cultures with growth. Â Results A total of 682 students were enrolled in the study comprising 602 boys (88%) and 80 girls (12%), 31 were suffering from the suspected disease i.e. tinea capitis. Of these, 30 patients i.e. 21 males (70%) and 9 females (30%) were confirmed mycologically to be suffering from tinea capitis accounting for 4.3% of all the studied subjects (p<0.001). The clinical features included itching in 27 patients (90%), scaling in 22 (73.4%) hair loss in 14 (46.6%), and lesions with discharge and erythema in 3 patients (10%). T. violaceum was the isolate in 27 patients (90%), while only three patients were culture positive for M. canis. Four students (0.58%, [p<0.001]), with no clinical signs and symptoms revealed positive cultures for T. violaceum. Â Conclusion Tinea capitis prevails amongst school going children, T. violaceum being the most common organism. Asymptomatic carriage of this organism may be a potential source for the anthroponotic spread of tinea capitis in this age group. Â